2021
DOI: 10.3390/nu13082717
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Eating Index-2015 Scores Vary by Types of Food Outlets in the United States

Abstract: Diet quality in the United States is improving over time but remains poor. Food outlets influence diet quality and represent the environments in which individuals make choices about food purchases and intake. The objective of this study was to use the Healthy Eating Index-2015 (HEI-2015) to evaluate the quality of foods consumed from the four major outlets where food is obtained—stores, full-service restaurants, quick-services restaurants, and schools—and to assess changes over time. This cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…An analysis of the 4 major outlets where food is obtained, that is, stores, quick-serve restaurants, full-service restaurants, and schools, using 24-hour dietary recall data from 8 cycles of the NHANES showed that Americans are not consuming foods that align with the Dietary Guidelines for Americans. 18 The HEI-2015 score for schools (65/100 points) and stores (62/100 points) was significantly higher than for full-service (51/100 points) and quick-service (39/100 points) restaurants ( P <0.0001).…”
Section: Nutritionmentioning
confidence: 85%
“…An analysis of the 4 major outlets where food is obtained, that is, stores, quick-serve restaurants, full-service restaurants, and schools, using 24-hour dietary recall data from 8 cycles of the NHANES showed that Americans are not consuming foods that align with the Dietary Guidelines for Americans. 18 The HEI-2015 score for schools (65/100 points) and stores (62/100 points) was significantly higher than for full-service (51/100 points) and quick-service (39/100 points) restaurants ( P <0.0001).…”
Section: Nutritionmentioning
confidence: 85%
“…Fruit, vegetables, and wholegrains intakes have been shown to be suboptimal in many Australians' diets [36,37] and are not always available in fast-food chain offerings, as documented in US restaurants and fast-food chains [38]. Another study using the MYMeals data showed that most main meals prepared at home were predominantly from the five food groups [39] defined in the Australian Guide to Healthy Eating as nutritious foods [40].…”
Section: Discussionmentioning
confidence: 99%
“…A radar graph was created to provide an illustration of how patients and caregivers obtained their overall HEI-2020 scores (https://epi.grants.cancer.gov/hei/interpret-visualize-hei-scores.html). 33 Each axis on the radar graph represents a unique component score. Component scores were graphed as percentages of the maximum possible score, for example, a Seafood and Plant Proteins score of 3/5 was graphed as 60%.…”
Section: Methodsmentioning
confidence: 99%